Peran Financial Technology Peer-To-Peer (P2p) Lending Dalam Mendukung Pengembangan Umkm Studi Kasus : Kampoeng Batik Laweyan - Bisthomi, Isa; Dwi Irawan, Januar; Qisti, Launa (UI Scholars Hub, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are the backbone of Indonesia's economy, absorbing 97% of the non-agricultural workforce and making a significant contribution to GDP. However, limited access to formal financing remains a major obstacle. Conventional banks often view MSMEs as high-risk, making it difficult for them to obtain loans. Peer-to-Peer (P2P) lending emerges as a technology-based solution, offering easier access to financing with lighter requirements and faster processes. This study aims to examine the role of P2P lending in enhancing financial inclusion and the capacity of MSMEs, focusing on the case study of Kampoeng Batik Laweyan in Solo. The research uses a normative juridical approach, combining legal analysis with field data. This study analyzes regulations related to P2P lending and its implementation in supporting MSMEs financial inclusion. The findings show that P2P lending not only improves access to financing but also fosters innovation, market expansion, and the sustainability of MSMEs. Strong regulation is needed to maintain public trust and ensure the sustainability of this sector. Therefore, P2P lending plays an important role in supporting the growth of inclusive and competitive MSMEs. It is recommended that the government strengthen regulations and provide training to MSMEs to utilize P2P lending as an alternative financing option that is more accessible.